2017
DOI: 10.1002/jmv.24785
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic characterization of circulating Dengue and Alkhumra Hemorrhagic Fever viruses in western Saudi Arabia and lack of evidence of Zika virus in the region: A retrospective study, 2010‐2015

Abstract: Flaviviruses represent a global public health concern. They consist of ∼70 viruses with almost half of them causing human diseases with unspecified febrile illnesses. Cities in western Saudi Arabia are endemic for viruses (DENV) with sporadic infections due to Alkhumra hemorrhagic fever virus (AHFV). They also represent a major destination for travelers coming for annual religious pilgrimages (Hajj and Umrah) from all over the world. However, whether other flaviviruses are circulating is not known because of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…In this context, several studies have shown independent multiple introductions of DENV-1 (lineage India-2 and lineage Asia-2) and DENV-2 (Cosmopolitan genotype and DENV-2-Jeddah-2014) in the Western province of the kingdom between the years 1994 and 2014 [10, 11, 25]. Additionally, the most recent report by the United Nations has estimated that 10 million migrant workers are living in KSA and many of them are from India and Pakistan where DENV-4 is endemic [28–30].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several studies have shown independent multiple introductions of DENV-1 (lineage India-2 and lineage Asia-2) and DENV-2 (Cosmopolitan genotype and DENV-2-Jeddah-2014) in the Western province of the kingdom between the years 1994 and 2014 [10, 11, 25]. Additionally, the most recent report by the United Nations has estimated that 10 million migrant workers are living in KSA and many of them are from India and Pakistan where DENV-4 is endemic [28–30].…”
Section: Discussionmentioning
confidence: 99%
“…At least four vector-borne viruses, including dengue virus (DENV), Alkhurma hemorrhagic fever virus, Rift Valley fever virus, and Crimean-Congo hemorrhagic fever virus have been circulating in Saudi Arabia [6]. The most important of them is dengue, with most of the disease burden and severity, mainly prevalent in the western and southwestern regions in Jeddah and Makkah, of Saudi Arabia [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Saudi Arabia was once a dengue-free country till the rst dengue outbreak in Jeddah in 1994 [11]. Now all the four DENV serotypes (DENV1-4) have been reported in Jeddah and Makkah [6,8,12]. Jeddah is the nancial and diplomatic center in Saudi Arabia, and is the major point-of-entry to the Holy city of Makkah (only 80 km SE of Jeddah) for millions of visitors of perennial religious rituals for pilgrimage (Hajj) and Umrah as well as workers and other visitors.…”
Section: Introductionmentioning
confidence: 99%
“…In western Saudi Arabia, three serotypes of DENV (DENV-1, DENV-2, and DENV-3) have been commonly isolated from 1994 to 2015 (7,8). Zaki et al 7performed a phylogenetic analysis of the DENV-2 E gene with strains isolated from Saudi Arabia between 1994 and 2004 and showed that all isolates belonged to the Cosmopolitan genotype.…”
mentioning
confidence: 99%